Evidence of Sulfur Non‐Innocence in [CoII(dithiacyclam)]2+‐Mediated Catalytic Oxygen Reduction Reactions. Issue 6 (29th December 2022) - Battistella, Beatrice; Iffland‐Mühlhaus, Linda; Schütze, Maximillian; Cula, Beatrice; Kuhlmann, Uwe; Dau, Holger; Hildebrandt, Peter; Lohmiller, Thomas; Mebs, Stefan; Apfel, Ulf‐Peter; Ray, Kallol
Abstract: In many metalloenzymes, sulfur‐containing ligands participate in catalytic processes, mainly via the involvement in electron transfer reactions. In a biomimetic approach, we now demonstrate the implication of S‐ligation in cobalt mediated oxygen reduction reactions (ORR). A comparative study between the catalytic ORR capabilities of the four‐nitrogen bound [Co(cyclam)] 2+ (1 ; cyclam=1, 5, 8, 11‐tetraaza‐cyclotetradecane) and the S‐containing analog [Co(S2 N2 ‐cyclam)] 2+ (2 ; S2 N2 ‐cyclam=1, 8‐dithia‐5, 11‐diaza‐cyclotetradecane) reveals improved catalytic performance once the chalcogen is introduced in the Co coordination sphere. Trapping and characterization of the intermediates formed upon dioxygen activation at the Co II centers in 1 and 2 point to the involvement of sulfur in the O2 reduction process as the key for the improved catalytic ORR capabilities of 2 . Abstract : A comparison of the abilities of two Co II complexes bearing N4 and S2 N2 ligations to mediate 2 e − /2 H + O2 reduction to H2 O2 reveals improved catalytic performance once the chalcogen is introduced in the Co coordination sphere. Trapping and characterization of the reactive intermediates point to the involvement of sulfur in the O2 reduction process as the key for the improved catalytic efficiency.